Role of Modern technology (Internet of things and Artificial Intelligence) in Agriculture: An Analytical Study - SRIVASTAV , SHASHANK (International Journal of Psychosocial Rehabilitation, 2024)
With the increasing demand for food globally, farmers are looking for ways to increase yields while reducing costs and improving sustainability. One solution to this challenge is the use of precision agriculture techniques. These cutting-edge technologies can be utilized to enhance crop productivity, optimize resource usage, and improve overall efficiency in farming practices. Two of the most important modern technologies are artificial intelligence (AI) and the internet of things (IoT), which can help farmers achieve these goals. IoT sensors can be used to collect real-time data on weather, soil moisture, and plant growth, which can then be analysed by AI algorithms to provide farmers with insights and recommendations for improving crop yields. AI-powered robots and drones can also be used to perform everyday and mundane tasks such as planting, weeding, and harvesting. These technologies have the potential to revolutionize agriculture by reducing labour costs, increasing efficiency, and improving sustainability. However, there are also concerns about the ethical and societal implications of AI and IoT in agriculture, such as the potential for job loss and the impact on small-scale farmers. This paper aims to analyze various aspects of the implementation of AI and IoT in modern agriculture.